THE INTEGRATION FORMULA TO FIND THE PARTICULAR SOLUTION FOR NONHOMOGENEOUS LINEAR ODE - Mahmood, Saad Shakir (MAGISTRA, 2011)
In this paper we proposed a new method to find the particular solution for the nonhomogeneous linearODE of higher order with constant coefficient.